The Effect of Career Development and Job Satisfaction on Nurses' Caring Behavior in Patients in Inpatient Hospital X Karawang in 2023 - Abdul Aziz (Jurnal Syntax Transformation, 2023)
Introduction to nurses' caring behavior when providing nursing care to clients that can improve the quality of nursing services and client safety which is certainly expected to help clients heal, but in reality to be able to realize the quality of nursing services is still experiencing obstacles, there is still a high number of uncaring behavior in providing services to patients, concrete steps are needed in solving the problem of high numbers Uncaring behavior through strengthening career development and nurse job satisfaction so that caring behavior can be realized. The purpose of this study was to determine the effect of career development and job satisfaction on the caring behavior of inpatient nurses at Hospital X Karawang. Non-experimental quantitative research method with cross sectional analytics using Logistic Regression, The sample of this study was 43 inpatient nurses of Hospital X Karawang with data analysis techniques using SPSS Program Version 24.0. The results based on multiple logistic regression analysis showed the influence of career development on nurses' caring behavior obtained p value of 0.009 (p-value < 0.05 ), there was an effect of job satisfaction on nurses' caring behavior obtained p value of 0.013 (p-value < 0.05). Based on multivariate analysis, there was an effect of career development and job satisfaction on nurses' caring behavior by 73.5%. In addition, the results of the study were obtained by respondents with good career development and have good caring behavior as many as 17 respondents with a percentage of 63% and respondents with less job satisfaction and have poor caring behavior as many as 16 respondents with a percentage of 66.7%. And it was obtained that more respondents in Hospital X Karawang Inpatient in 2023 had less job satisfaction, namely as many as 24 (55.8%) respondents. Conclusion Based on the results of this study, it can be concluded that of the 2 variables studied, the most dominant variable affecting Caring Behavior is the Career Development variable with a value with an odds ratio value of 3.551, but nevertheless does not ignore other variables such as Job Satisfaction with an odds ratio value of 2.924 54. Career development is the biggest influence that affects nurses' caring behavior in patients at Inpatient Hospital X Karawang.